Legal Positivism and Fiqh Muamalah Paradigm’s on Indonesian Sharia Fintech Legal Framework - Saifullah, Saifullah; Al Munawar, Faishal Agil; Bahagiati, Kurniasih; Supriyadi, Aditya Prastian (Faculty of Sharia and Law, UIN Syarif Hidayatullah Jakarta, 2024)
Sharia Financial Technology in Indonesia is regulated in OJK Regulation No. 10/POJK.05/2022 Concerning Information Technology-Based Joint Funding Services. According to researchers, enacting these regulations still needs improvement because they are disproportionate to the basic rules for implementing Sharia Fintech in Indonesia. A Fiqh Muamalah study needs to be conducted to reconstruct these rules into proportional rules. This research uses normative legal research methods. This research uses a statutory regulatory approach related to Fintech and DSN MUI Fatwa, as well as the Fiqh Muamalah conceptual approach. The results show that based on the Fiqh Muamalah indicator, OJK Regulation No. 10/POJK.05/2022 still needs to be in harmony with Fiqh Muamalah. The OJK Regulations have no concrete rules regarding what contracts can be used for Sharia Fintech schemes. Abstrak:Financial Technology Syariah di Indonesia saat ini diatur dalam Peraturan OJK No. 10/POJK.05/2022 Tentang Layanan Pendanaan Bersama Berbasis Teknologi Informasi. Keberlakuan Peraturan tersebut masih perlu di perbaiki karena tidak proporsional sebagai aturan dasar penyelenggaraan. Perlu ada kajian Fikih Muamalah untuk Merekonstruksi aturan tersebut menjadi aturan yang proporsional. Penelitian ini menggunakan metode penelitian hukum normatif. Pendekatan penelitian menggunakan Pendekatan Peraturan Perundang-undangan yang terkait dengan Fintech dan Fatwa DSN MUI, serta pendekatan Konseptual Fikih Muamalah. Hasil Penelitian menunjukkan, berdasarkan indikator Fikih Muamalah, Peraturan OJK No. 10/POJK.05/2022 masih tidak harmonis dengan Fikih Muamalah. Dalam Peraturan OJK tidak ada aturan konkret mengenai akad apa yang dapat digunakan untuk skema Fintech Syariah.